Pelatihan Pemanfaatan Game Edukatif Rangkar Ultra Sebagai Media Pembelajaran Zat Aditif - Uliyandari, Mellyta Mellyta; Sutarno, Sutarno Sutarno; Nirwana, Nirwana Nirwana (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2024)
This service aims to provide training on the use of the educational game Rangkar Ultra (Circular Chain of Giant Snakes and Ladders) as an alternative learning media for additives at MTS Ja- Alhaq, Bengkulu City. This service involved 80 class VII students at MTS Ja-Alhaq, Bengkulu City. The service was carried out using the Technical Assistance Model method in the form of training activities and mentoring activities. The training activities were carried out by delivering material about additives in food and then providing information about the rules and regulations. how to use the educational game Rangkar Ultra. Meanwhile, mentoring activities are carried out after carrying out the previous activities, namely by practicing the educational game Rangkar Ultra to increase students' interest and motivation to learn. The result of this service activity is that students can utilize the Rangkar Ultra educational game as an innovative learning medium to increase motivation and interest in learning for class VII students at MTS Ja-Alhaq, Bengkulu City.